Chilling-Susceptibility of the Blue-Green Alga Anacystis nidulans: III. LIPID PHASE OF CYTOPLASMIC MEMBRANE - Ono, Taka-Aki (1982)
The lipid phase of cytoplasmic membrane was studied by freeze-fracture electron microscopy in the chilling-susceptible blue-green alga, Anacystis nidulans. At growth temperatures, intramembrane particles were distributed at random in the fracture faces of cytoplasmic membrane, whereas, at chilling temperatures, the fracture faces were composed of particle-free and particle-containing regions. These findings indicate that lipids of the cytoplasmic membrane were in the liquid-crystalline state at the growth temperatures and in the phase-separation state at the chilling temperatures. Temperatures for the onset of phase separation were 5 and 16°C in cells grown at 28 and 38°C, respectively. In comparison, another blue-green alga, Anabaena variabilis, which is not susceptible to chilling, was also examined by the freeze-fracture electron microscopy. The intramembrane particles were distributed at random in the fracture faces of cytoplasmic membrane at the growth, as well as at the chilling, temperatures. The results in this and previous studies suggest that the chilling susceptibility of A. nidulans is a result of irreversible leakage of ions from the cytoplasm when the lipids of cytoplasmic membrane are in the phase-separation state at low temperatures.